2017
DOI: 10.1590/1982-43272766201708
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Perceptions of Stress and Future Expectations

Abstract: Adolescence has been described as a developmental phase marked by challenges, tensions, and uncertainties that can generate stress and lower adolescents' future expectations. This study aims to describe adolescent perceptions of stress and future expectations. It is a mixed-methods study of 17 high school students, selected from a sample of 295 adolescents, aged 14 to 18 years, who are pupils in a private school system in the metropolitan region of Belém do Pará. The Stress Scale for Adolescents was used, in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
5
0
4
Order By: Relevance
“…Two of these studies explored the triggers or stressors experienced by adolescents. Florêncio, Ramos, and Silva (2017) conducted focus groups with 17 adolescents. Interestingly, adolescents with high stress indicated that family, and relationships were primary contributors to their stress, whereas adolescents with low stress reported that family and relationships were sources of positivity and calm.…”
Section: Qualitative Studies Of Stress and Headaches In Adolescentsmentioning
confidence: 99%
“…Two of these studies explored the triggers or stressors experienced by adolescents. Florêncio, Ramos, and Silva (2017) conducted focus groups with 17 adolescents. Interestingly, adolescents with high stress indicated that family, and relationships were primary contributors to their stress, whereas adolescents with low stress reported that family and relationships were sources of positivity and calm.…”
Section: Qualitative Studies Of Stress and Headaches In Adolescentsmentioning
confidence: 99%
“…Positive relations with family and social environment affect expectations of adolescents on the future positively. Feeling of burnout in adolescences may occur with youth whose expectations are disappointed and unrealized (Florêncio et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Desde a adolescência e nas primeiras fases da vida adulta, os fatores estressores afetam negativamente a perspectiva profissional de um jovem estudante, fato evidenciado ao se comparar um grupo de indivíduos considerados estressados e não demonstrarem expectativas, e um sem estresse, que já havia objetivos e planos bem delineados (Florêncio, Ramos, & Silva, 2017;Garcia, Ramos, & Bassalo, 2020).…”
Section: Introductionunclassified
“…A gestão do tempo no cotidiano acadêmico ganha destaque com a flexibilização das opções de aulas presenciais por oferta de carga horária na modalidade de Ensino a Distância (EaD), exigindo do estudante uma disciplina na organização do tempo, horário e ritmo de estudo no decorrer da graduação (Portaria n. 2.117, 2019;Florêncio, Ramos, & Silva, 2017).…”
Section: Introductionunclassified